Analyze the Association of Depression and Anxiety in Patients with and without Pandemic Disease Covid-19 - Ghulam Hassan, Nauman Mazhar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to compare the prevalence of depression and anxiety in people with and without COVID-19. Study Design: Cross-sectional Place and Duration: Sahara Medical College / Sughra Shafi Medical Complex Narowal. Feb-2021-Aug 2021 Methods: In this study, 178 cases of both sexes had age 15-55 years were presented. After obtaining written consent, the patient’s complete demographic information—including age, sex, and BMI—was collected. Two groups of patients were split evenly. Group M contained 89 COVID-19 patients, while group N contained 89 cases but did not contain COVID-19. Both groups’ rates of depression and anxiety were assessed. It was decided to use structural questionnaires. SPSS 18.0 was used to analyze all the data. Results: Among 178 cases, 104 (58.4%) were males and 74 (41.6%) were females. Majority of the cases 80 (44.9%) had age 18-30 years, 65 (36.5%) had age 31-40 years and 33 (18.5%) had age >40 years. 120 (67.4%) had BMI <25kg/m2 and 58 (33.6%) had BMI >25kg/m2. We found significantly higher number of depression 48 (53.9%), anxiety 30 (33.7%) and stress 19 (21.3%) in patients of group M as compared to group N found in 24 (26.9%), 18 (16.9%) and 11 (12.4%) with p value <0.005. Conclusion: In this study, we found that, in comparison to non-COVID 19 patients, COVID-19 patients typically experienced significant levels of anxiety and depression. Patients with medical conditions should learn methods for quick identification and treatment of depression and anxiety. Keywords: COVID-19, anxiety, depression, illness